Rolled vs. finely ground pelleted sorghum grain in cattle rations - Richardson, D.; Smith, E.F.; Koch, B.A.; Tsien, W.S.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Twenty Hereford steer calves were divided as equally as possible on the basis of weight and conformation into two lots of 10 animals each. The average daily rations are shown in Table 22 for the wintering and fattening phases. The ingredients were the same in both lots except rolled grain was used in lot 1 and finely ground pelleted grain in lot 2. The concentrate part of the ration was kept constant, with all the roughage the animals would clean up.
Keywords: Beef; Rolled vs. finely ground pelleted sorghum; Carcass grades